If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+2-(x-4)=x-1
We move all terms to the left:
x+2-(x-4)-(x-1)=0
We get rid of parentheses
x-x-x+4+1+2=0
We add all the numbers together, and all the variables
-1x+7=0
We move all terms containing x to the left, all other terms to the right
-x=-7
x=-7/-1
x=+7
| 16=4x*x | | 1/4n+9=13 | | 2/5z=18 | | 5x+3}+3=11 | | 11=z/8 | | 21/2=1/y | | |(5x-1)/4|=6 | | (M+2)(m+3)=0 | | 2m^+10m=0 | | 1.5x+2-8=68-24/3-48x | | 25x-5x=10 | | f+20–7=–6 | | 2/x+5=1-x+1/5 | | 9x+3x+10=46 | | 3.111111x=1.666667 | | 3-13x=29 | | X/7+x/14=9 | | 11x-9=4x+9 | | ⅓x-1=½x+2 | | |3x-4|=|-x-18| | | 0.331x-1=0.5x+2 | | 6x2-75=0 | | 3+x=2.25 | | 8=4+5a | | 2h=24h | | 11-3(q-4)=8q+4 | | 3x-9=-(X+3) | | 9^(x-1)=3^(1-4x) | | 4x-2=-(2x+8) | | 3(6x–4)=22x* | | (3x-11)(3x-11)=0 | | 6t-10=4+12 |